The Little Owl : conservation, ecology and behavior of Athene noctua - Van Nieuwenhuyse, Dries, ....-; Génot, Jean-Claude, ....-; Johnson, David H., ....- (Cambridge : Cambridge University Press, 2010)
Our understandig of the basic biology of owls is poor compared with that of other bird species. The Little Owl, Athene noctua, has become one of the best models for biological and conservation research, due to its commonness and the fact that it occupies nest-boxes very easily. In this unique book the authors synthesize the substantial literature, and detail current information regarding the Little Owl. They discuss its wide-ranging ecology, genetics and subspecies, and population status by country. In addition, they outline a strategy and monitoring program for its conservation. The book features an outstanding bibliography of literature on the Little Owl, listing publications dated from 1769 through to 2007, in many languages, including Russian, English, French, German, Spanish, Portuguese, Italian and Dutch. Whilst being an invaluable resource for academic researchers, its straightforward style holds undoubted appeal for amateurs and enthusiasts.
Keywords: Steenuil